The Microbial Opsin Homolog Sop1 is involved in Sclerotinia sclerotiorum Development and Environmental Stress Response - Lyu, Xueliang; Shen, Cuicui; Fu, Yanping; Xie, Jiatao; Jiang, Daohong; Li, Guoqing; Cheng, Jiasen (Frontiers in Microbiology, 2016)
Microbial opsins play a crucial role in responses to various environmental signals. Here, we report that the microbial opsin gene sop1 in the necrotrophic phytopathogenic fungus Sclerotinia sclerotiorum was dramatically up-regulated during infection and sclerotial development compared with the vegetative growth stage. Further study showed sop1 was essential for growth, sclerotial development and full virulence of S. sclerotiorum. Sop1-silenced transformants were more sensitive to high salt stress, fungicides and high osmotic stress. However, they were more tolerant to oxidative stress compared with the wild-type strain, suggesting that sop1 is involved in different stress responses and fungicide resistance, which plays a role in the environmental adaptability of S. sclerotiorum. Furthermore, a Delta blast search showed that microbial opsins are not present in animals and almost all higher plants, indicating that as a predicted transmembrane protein, sop1 is a potential drug target for disease control of S. sclerotiorum.